Rationalizing the GMO debate: The ordonomic approach to addressing agricultural myths - Stefan Hielscher; Ingo Pies; Vladislav Valentinov; Lioudmila Chatalova (International Journal of Environmental Research and Public Health, 2016)
The public discourse on the acceptability of genetically modified organisms (GMOs) is not only controversial, but also infused with highly emotional and moralizing rhetoric. Although the assessment of risks and benefits of GMOs must be a scientific exercise, many debates on this issue seem to remain impervious to scientific evidence. In many cases, the moral psychology attributes of the general public create incentives for both GMO opponents and proponents to pursue misleading public campaigns, which impede the comprehensive assessment of the full spectrum of the risks and benefits of GMOs. The ordonomic approach to economic ethics introduced in this research note is helpful for disentangling the socio-economic and moral components of the GMO debate by re- and deconstructing moral claims.
Keywords: 330; agricultural myths; discourse; ethics; GMO; morality; ordonomics